Evaluation of The Intangible Cultural Heritage in The Context of Conservation and Sustainability of Historical Settlements in Anatolia - Akyildiz, Uyesi Nihal Arda; Olgun, Tuba Nur (Geleneksel Yayincilik Ltd Stl, 2020)
Intangible cultural heritage is effective as well as tangible heritage in the conservation of historical and traditional settlements. In settlements and structures where culture is not conserved, only physically conservation practices are made, it is not possible for conservation practices to have sustainable qualifications. Evaluation of tangible and intangible cultural heritage as a whole and implementation of these practices taking into account this evaluation; it is of great importance in terms of transmitting architectural heritage to future generations correctly. In this context, Anatolia emerges as a rich area with its heritage, in which both tangible and intangible cultural heritage and practices related to conservation and sustainability can be addressed in detail. It is not only in our country with its deep-rooted history and cultural heritage; Anatolia, which has an important place all over the world, contains many values that must be conserved in this context and transmitted to future generations. Historical and traditional settlements have an important place in these values in many ways. Attracting the attention of many civilizations with its strategic location and the resources it contains, Anadolu has traces from almost all of these civilizations in every point from east to west. The aim of the study is to reveal the effects of intangible cultural heritage on the conservation and sustainability of historical and traditional settlements through Anatolia, a rich example in this sense. The study includes a perspective on the conservation and sustainability of historical settlements in the context of intangible cultural heritage and field studies of Manisa-Kula, Konya-Sille and Malatya-Balaban from Anatolia. The investigated settlements stand out with their qualities in terms of the relationship of the intangible cultural heritage with space. Literature researches and on-site investigations are the main methods of the study. It is thought that the data obtained as a result of the study will contribute to the understanding of the importance of intangible cultural heritage in the context of the conservation and sustainability of architectural heritage and historical settlements.
Keywords: Intangible cultural heritage; Anatolia; historical and traditional settlements; conservation; sustainability